Ophioglossum hongii (Ophioglossaceae), a new species from Xizang, China - Li, Min-Yu; Yang, Fu-Sheng; Yan, Yue-Hong; Chen, Li-Jun; Huang, Zhi-Cong; Shu, Jiang-Ping; Qin, Xin-Sheng (Phytotaxa, 2024)
Ophioglossum hongii (Ophioglossaceae) is described as a new species from the plateau area of Xizang, China. It was recorded as the species O. nudicaule previously, but obviously differs in its shorter sporophores and the conspicuous persistent petiole bases at the top of rhizome. O. hongii is similar to O. polyphyllum in morphology, but it can be distinguished from the latter by plant size, trophophyll shape, fertile stalk and exospore ornamentation. O. hongii is the sister to the clade (O. polyphyllum, O. engelmannii) according to molecular phylogenetic analysis of seven plastid fragments (atpB, matK, psbA-trnH, rbcL, rps4, rps4-trnS, and trnL-F). Detailed taxonomic description, distribution, ecology, conservation status and chloroplast genome resources are provided.